The Genome of C57BL/6J "Eve", the Mother of the Laboratory Mouse Genome Reference Strain. Issue 6 (1st June 2019) - Sarsani, Vishal Kumar; Raghupathy, Narayanan; Fiddes, Ian T; Armstrong, Joel; Thibaud-Nissen, Francoise; Zinder, Oraya; Bolisetty, Mohan; Howe, Kerstin; Hinerfeld, Doug; Ruan, Xiaoan; Rowe, Lucy; Barter, Mary; et al.
Abstract: Isogenic laboratory mouse strains enhance reproducibility because individual animals are genetically identical. For the most widely used isogenic strain, C57BL/6, there exists a wealth of genetic, phenotypic, and genomic data, including a high-quality reference genome (GRCm38.p6). Now 20 years after the first release of the mouse reference genome, C57BL/6J mice are at least 26 inbreeding generations removed from GRCm38 and the strain is now maintained with periodic reintroduction of cryorecovered mice derived from a single breeder pair, aptly named Adam and Eve. To provide an update to the mouse reference genome that more accurately represents the genome of today's C57BL/6J mice, we took advantage of long read, short read, and optical mapping technologies to generate a de novo assembly of the C57BL/6J Eve genome (B6Eve). Using these data, we have addressed recurring variants observed in previous mouse genomic studies. We have also identified structural variations, closed gaps in the mouse reference assembly, and revealed previously unannotated coding sequences. This B6Eve assembly explains discrepant observations that have been associated with GRCm38-based analyses, and will inform a reference genome that is more representative of the C57BL/6J mice that are in use today.